Pengaruh Metode Kooperatif Number Head Together (NHT) dan Mind Mapping terhadap Hasil Belajar Siswa Mata Pelajaran PAI di SMA Taruna Andigha Kota Bogor. - Elok Mufidah (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Learning outcomes in the subjects of Islamic Religious Education and manners in the material of Hajj, Zakat and waqf of 10th grade students of SMA Taruna Andigha Bogor City are still low. Judging from the data on the learning outcomes of 10th graders in the 2021/2022 academic year, it was found that 36 students (45%) of 80 students achieved the KKM score, namely 75 and 44 students (55%) of 80 students. which is not complete on the material of pilgrimage, zakat and waqf. . This happens because in the delivery of subject matter the teacher emphasizes knowledge to be memorized. The learning method used by the teacher is dominated by the lecture method. More students sit still, and are given assignments only when learning takes place. As a result, students tend to be bored with learning. This problem must be resolved immediately. Steps that can be taken to solve the problem are by changing the learning method used which focuses more on student activity. To overcome these problems, a research entitled